2010
DOI: 10.1016/j.biopsycho.2010.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Metabolically exaggerated cardiac reactions to acute psychological stress: The effects of resting blood pressure status and possible underlying mechanisms

Abstract: The study aimed to: confirm that acute stress elicits metabolically exaggerated increases in cardiac activity; test whether individuals with elevated resting blood pressure show more exaggerated cardiac reactions to stress than those who are clearly normotensive; and explore the underlying mechanisms. Cardiovascular activity and oxygen consumption were measured pre-, during, and post- mental stress, and during graded submaximal cycling exercise in 11 young men with moderately elevated resting blood pressure an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 37 publications
2
30
0
Order By: Relevance
“…1 The present results add further weight to the contention that individuals with disordered eating may have a dysregulated stress response Lo Sauro et al, 2008). The precise pattern of the present group differences, with the disordered eating group showing blunted cardiac reactivity and attenuated systemic vasodilatory reactions to stress, would seem to implicate b-adrenergic processes (Balanos et al, 2010). It is possible that the disordered eating behaviour is associated with diminished badrenergic activation.…”
Section: Discussionmentioning
confidence: 74%
“…1 The present results add further weight to the contention that individuals with disordered eating may have a dysregulated stress response Lo Sauro et al, 2008). The precise pattern of the present group differences, with the disordered eating group showing blunted cardiac reactivity and attenuated systemic vasodilatory reactions to stress, would seem to implicate b-adrenergic processes (Balanos et al, 2010). It is possible that the disordered eating behaviour is associated with diminished badrenergic activation.…”
Section: Discussionmentioning
confidence: 74%
“…Second, given the oral response mode in the PASAT, cardiovascular perturbations could be attributed to speech. However, similar levels of HR reaction to mental arithmetic with and without a speech component have been reported (Sloan et al, 1991) and we have reported substantial cardiovascular reactions to the PASAT when the mode of response was manual rather than oral Balanos et al, 2010). Third, only blood pressure and HR reactivity were measured.…”
Section: Youngmentioning
confidence: 68%
“…There were no consistent associations between blood pressure reactivity and future cognitive ability. Cardiac reactivity would appear to reflect both β-adrenergic and parasympathetic influences (Balanos et al, 2010;Sloan et al, 1991). Thus, low cardiac reactivity could reflect reduced β-adrenergic drive or less of a reduction in vagal tone during the stress task.…”
Section: Youngmentioning
confidence: 95%
“…Consistent with the earlier studies, the psychological stressor did result in greater increases than would be expected on the basis of metabolic demand. Balanos et al (2010) followed up this study by finding that the exaggerated cardiac responses seen during the PASAT task indicated greater beta-adrenergic activation than parasympathetic response.…”
Section: Introductionmentioning
confidence: 97%